Imipenem heteroresistance in nontypeable Haemophilus influenzae is linked to a combination of altered PBP3, slow drug influx and direct efflux regulation. (February 2017) - Cherkaoui, A.; Diene, S.M.; Renzoni, A.; Emonet, S.; Renzi, G.; François, P.; Schrenzel, J.
Abstract: Objective: To investigate the potential roles of PBPs, efflux pumps and slow drug influx for imipenem heteroresistance in nontypeable Haemophilus influenzae (NTHi). Methods: Fifty-nine NTHi clinical isolates examined in this study were collected at Geneva University Hospitals between 2009 and 2014. Alterations in PBPs were investigated by gene sequencing. To evaluate the affinities of the PBPs to imipenem, steady-state concentration–response experiments were carried out using imipenem in a competition assay with Bocillin-FL. The effect of the carbonyl cyanide m -chlorophenylhydrazone (CCCP) on imipenem susceptibility was assessed using broth dilution and viable cell counting. Using whole-genome sequencing, we explored the potential roles of outer membrane protein P2 (OmpP2), LytM proteins and the dcw gene cluster in imipenem heteroresistance. Results: All 46 imipenem-heteroresistant isolates (IMI hR ) harboured amino acid substitutions in the ftsI gene, which encodes PBP3, corresponding to 25 different mutation patterns that varied from the ftsI gene mutation patterns found in imipenem-susceptible isolates. Among all PBPs, the highest affinity to imipenem was documented for PBP3 (IC50, 0.004 μg/mL). Different amino acid substitutions and insertions were noted in OmpP2, suggesting a relationship with imipenem heteroresistance. The IMI hR isolates were affected by CCCP differently and displayed a higher percentage of killing by imipenem in CCCP-treated cells at concentrations ranging between 0.5 and 8 μg/mL. Conclusions: The present study provides robust evidence indicating that in combination with the altered PBP3, the slowed drug influx and its enhanced efflux due to the loss of regulation led to the development of imipenem heteroresistance in NTHi.